Design of Protection Coordination for Overcurrent on Electrical System in Tanker Ship Plan Using Electro Mechanical Trip Device - Indra Ranu Kusuma; Eddy Setyo Koenhardhono; Riantini Karmina (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2017)
Disturbance of power system in ship is unavoidable case that required a function from safety system to separate the affected parts of system. The disturbance in electrical system generally is a short-circuit current. It is affected when there are two conductors having lowest impedance in normal condition that have two different voltages thus causing an overcurrent. There is one of the device protection to prevent a disturbance like short circuit current, is circuit breaker. It opens the contact with component or system that disturbance using electromechanical trip device. The principal operating of trip device is using electric current flow in the circuit breaker and the magnet induces the tripping part to moving the contact from closed position to the opened position. The main discussion is to coordinate circuit breakers in four operating conditions of the ship's generator using software ETAP. The simulation of the result obtained value of short circuit in main bus one at sailing condition is 8.2 kA. Tripping time for the circuit breakers in sailing condition at one typical disturbance are 0.75 seconds for circuit breaker number 29; 0.83 seconds for circuit breaker number 37 and 1 second for circuit breaker number 28.